2013
DOI: 10.3899/jrheum.121118
|View full text |Cite
|
Sign up to set email alerts
|

Subcutaneously Administered Ofatumumab in Rheumatoid Arthritis: A Phase I/II Study of Safety, Tolerability, Pharmacokinetics, and Pharmacodynamics

Abstract: Objective.To investigate the safety and tolerability of a single subcutaneous (SC) dose of ofatumumab, a fully human anti-CD20 monoclonal antibody, in patients with rheumatoid arthritis (RA) taking background methotrexate (MTX). Secondary objectives included characterizing pharmacokinetics and pharmacodynamics.Methods.In this single-blind, phase I/II study, 35 patients with RA were randomized in 5 cohorts to receive a single subcutaneous (SC) ofatumumab dose ranging from 0.3 to 100 mg, or placebo, following pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(24 citation statements)
references
References 17 publications
0
23
0
1
Order By: Relevance
“…As an alternative to the IV route and to eliminate the need for premedication with glucocorticoids, a SC formulation was investigated with the rationale that SC ofatumumab could achieve a slower rate of absorption and B cell depletion and potentially improve safety and tolerability. The sponsors began testing a SC formulation of ofatumumab in a 24-week phase I/II, single-blind trial with extended follow-up for up to 2 years to evaluate its safety and tolerability in RA patients who failed MTX [ 19 ]. Patients received a single SC injection of ofatumumab at 0.3, 3, 30, 60, or 100 mg doses or placebo with oral antihistamine and acetaminophen premedication.…”
Section: Anti-cd20 Mabs In Rheumatoid Arthritismentioning
confidence: 99%
See 2 more Smart Citations
“…As an alternative to the IV route and to eliminate the need for premedication with glucocorticoids, a SC formulation was investigated with the rationale that SC ofatumumab could achieve a slower rate of absorption and B cell depletion and potentially improve safety and tolerability. The sponsors began testing a SC formulation of ofatumumab in a 24-week phase I/II, single-blind trial with extended follow-up for up to 2 years to evaluate its safety and tolerability in RA patients who failed MTX [ 19 ]. Patients received a single SC injection of ofatumumab at 0.3, 3, 30, 60, or 100 mg doses or placebo with oral antihistamine and acetaminophen premedication.…”
Section: Anti-cd20 Mabs In Rheumatoid Arthritismentioning
confidence: 99%
“…Due to the high rate of IRRs with IV ofatumumab and the favorable safety profile demonstrated by a phase I/II trial for SC ofatumumab in RA patients [ 19 ], a study of SC ofatumumab in MS was conducted. The MIRROR trial was a 24-week phase II, randomized, double-blind, placebo-controlled, parallel-group, dose-ranging study in RRMS in which ofatumumab was administered as SC injections [ 26 ].…”
Section: Anti-cd20 Mabs In Multiple Sclerosismentioning
confidence: 99%
See 1 more Smart Citation
“…A trial with subcutaneous ofatumumab in patients with RA on background MTX showed profound and prolonged B cell depletion without required glucocorticoid premedication. 41 …”
Section: New Biologicalsmentioning
confidence: 99%
“…Results of the initial dose-ranging study [ 13 ] and the 24-week, double-blind, placebo-controlled period of the Phase III study in biologic-naive MTX-refractory patients [ 14 ] indicated that the short-term efficacy and safety of intravenous ofatumumab in RA was similar overall to that observed with other anti-CD20 therapies [ 8 , 15 ]. Furthermore, consistent with the high potency of ofatumumab, a single-blind phase I/II trial in RA patients on background MTX demonstrated that even single subcutaneous formulation doses of ofatumumab, as low as 30 mg, were able to induce profound and persistent peripheral B-cell depletion [ 16 ]. Based on the encouraging results of the subcutaneous study, the clinical development of the intravenous formulation of ofatumumab in RA was discontinued and the three ongoing RA trials were prematurely terminated in favour of initiating a clinical development programme to evaluate the effects of subcutaneously administered ofatumumab in autoimmune diseases instead.…”
Section: Introductionmentioning
confidence: 99%